Urgensi Administrasi Guru dalam Kegiatan Belajar Mengajar - Fatimah, Meti; Thoriq, Jamal; Ardianto, Risko Aris (TSAQOFAH, 2024)
Teacher administration and teaching and learning activities are two important entities in the world of education. The existence of teacher administration is needed to support teaching and learning activities. The aim of this research is to explore the importance of teacher administration to the success and quality of teaching and learning. The method used in this research is literature study. Data collection was carried out by reading a collection of scientific articles/journals and books in various digital library institutions and the internet. The analysis was carried out based on similar research as well as studies of various theories regarding teacher administration, learning and teaching and learning activities. From the results of the analysis carried out, it was found that although teacher administration does not have a significant influence on the quality of learning, its existence must still be used as a guide in designing teaching and learning activities. The interactions that occur between teachers and students in learning are very much determined by the teacher's preparation and supporting facilities.